Analisis Desain Faktorial Pengaruh Variabel Proses terhadap Kualitas Permukaan Potong pada Proes Laser Cutting - Totok Suwanda; Dinda Aliunnisa (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Laser cutting is a precise and efficient manufacturing technology, but process parameters significantly influence the quality of the cut surface. A smooth cut surface is one of the essential criteria in laser metal cutting, especially in the manufacturing industry. The roughness of the cut surface is influenced by several key parameters, including the laser beam focal point, and optimal cutting gas pressure can help clean the surface. This study aims to analyze the effects of process variables on the roughness of the cut surface in laser cutting. Experiments were conducted with a combination of three variables, namely cutting speed, gas pressure, and focal point, on 3 mm mild steel material using the factorial design method. The results showed that the optimal parameter combination for the lowest surface roughness was a cutting speed of 2.3 m/min, a gas pressure of 1.8 bar, and a focal point of 4.3 mm. The cutting speed and gas pressure variables have a significant effect on surface quality, and the interaction between cutting speed and focal point also significantly affects surface roughness.